2014
DOI: 10.1111/1750-3841.12500
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Exogenous Hyaluronan on the Behavior of Human Cancer Cells or Endothelial Cell Capillary Formation

Abstract: Orally administered hyaluronan was recently found to have beneficial effects. However, the effect of exogenous hyaluronan on cancer remains unclear. Our findings support the safety of orally administered hyaluronan and its use as a functional food ingredient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Interestingly, the results revealed that treatment with HA of different sizes had no specific effect on CRC malignancy. This finding is consistent with some recent reports that the HA ligand‐related pathway has no effect on regulating cellular behavior …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the results revealed that treatment with HA of different sizes had no specific effect on CRC malignancy. This finding is consistent with some recent reports that the HA ligand‐related pathway has no effect on regulating cellular behavior …”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with some recent reports that the HA ligand-related pathway has no effect on regulating cellular behavior. 37,38 Our results demonstrated that secreted HA ligand has less influence on CRC; however, overexpressed HAS2 regulates CRC malignancy crucially. This led us to postulate that HAS2 has a specific role in CRC malignancy regulation independent of HA synthase.…”
Section: Overexpression Of Has2 Mediates Colorectal Cancer Malignanmentioning
confidence: 72%
“… 26 In addition, various safety studies were also conducted, and safety was confirmed. 27 – 37 Therefore, HA can be said to be a food material, which is suitable for long-term continuous intake.…”
Section: Discussionmentioning
confidence: 99%
“…No toxicity was observed in single-dose toxicity studies [ 48 – 50 ], repeated-dose toxicity studies [ 51 – 61 ], reproductive and developmental toxicity studies [ 62 – 69 ], mutagenicity tests [ 70 – 74 ], and antigenicity studies [ 75 , 76 ]. It is reported that exogenous HA such us that administered orally is not harmful to human cancer cells [ 77 ]. A 12 month clinical study identified no adverse event attributable to HA [ 41 ].…”
Section: Safety Of Hamentioning
confidence: 99%